IMPLEMENTASI PEMBELAJARAN MENGHAFAL AL-QUR’AN DI SD IT IRSYADUL IBAD DAN SD BAHRIATUL ULUM KABUPATEN PANDEGLANG - Ipat Fatimah; Cecep Nikmatullah; Tatu Maesaroh; Ahmad Mussaddiq (QATHRUNÂ, 2022)
The purpose of the research is to know the learning to memorize the Qur’an at SD IT Irsyadul Ibad and SD Bahriatul Ulum Pandeglang. Field research method, type of case study research and comparative descriptive. The results showed that learning to memorize the Qur’an at SD IT Irsyadul ‘Ibad through Ummi method with 7 stages. (a) starting 09.30-10.00 WIB for class IV-VI only; (b) planning stage; 35 minutes, U-shaped position, in groups of 3-14 students, classic model read and listen, Ummi’s book. (c) Implementation of learning according to the Ummi method and target group by rote, class I memorizing and class II-VI memorizing and muraja’ah. Supporting factors; teacher as a professional teacher and Ummi’s book. Inhibiting factors: the lack of teachers and students’ abilities are different. Meanwhile, SD Bahriatul Ulum uses Iqra method. (a) Monday-Friday 07.30-11.00; (b) planning stage; according to procedures, materials according to targets, methods applied by students, assessment sheets, planning and teacher administration. (c) implementation of learning according to the method. Supporting factors: (a) the ability of teacher to read the Qur’an is very good, (b) physically and psychologically good, (c) parental support, (d) teacher support. Inhibiting factors: (a) students are less enthusiastic, (b) students are less concentrated, (c) students are tired when memorizing, and (d) students are weak in memorizing. Suggestions for supervising teachers should follow the rules of learning to memorize the Qur’an and the stages of the school. Therefore, further research is needed, as an effort to develop broader and in-depth research.